EXTENDED MEASURES OF RESTRICTIONS TO CAPITAL ACCOUNT TRANSACTIONS - Selaive, Jorge (Estudios de Economía, 2016)
In this work we extend a De Jure measure of capital account restrictions, previously assembled by Miniane (2004) for 34 economies, to a set of 181 countries for the period 1996-2005. Additionally, having in mind the pitfalls of this indicator, we propose two new measures. The first excludes prudential regulation and the second weights the indicator by a proxy of enforcement. This group of indicators allows academics and policymakers to evaluate and analyze the restrictions to capital account transactions for a large group of economies.